GENDER-SPECIFIC NUTRITIONAL STRATEGIES: COMPARING MALE AND FEMALE BODYBUILDERS' DIETARY APPROACHES DURING COMPETITION PREPRATION (International Journal of Food and Nutritional Sciences, 2022)
This abstract examines the specific dietary approaches employed by male bodybuilders during their competition preparation phase. The analysis focuses on the unique nutritional requirements and strategies that cater to the physiological makeup of male athletes in this demanding sport. Key areas of discussion include macronutrient manipulation, with emphasis on high protein intake and strategic carbohydrate management. The abstract explores the typical caloric ranges utilized, which are generally higher than those of their female counterparts due to greater muscle mass and basal metabolic rates. Additionally, it touches upon the gradual reduction of body fat while maintaining muscle mass, common supplement usage, and the practice of carb cycling. The abstract also addresses the potential for more aggressive calorie deficits in male bodybuilders and the shorter preparation periods often required compared to females. This comprehensive overview provides insights into the nuanced nutritional approach necessary for male bodybuilders to achieve peak physical condition for competition.